Cutaneous Bacillary Angiomatosis: A Rare and Forgotten Infection in Immunocompromised Patient - Homsi, Yamen; Milam, Emily; Dayoub, Nour (Avicenna Journal of Medicine, 2025)
This case describes a 50-year-old kidney transplant recipient with subacute development of erythematous-to-violaceous skin lesions on the face, trunk, and extremities, accompanied by malaise, myalgia, and arthralgia. Histopathologic analysis of skin biopsies revealed characteristic vascular proliferation consistent with bacillary angiomatosis (BA), a rare angioproliferative disease caused by Bartonellahenselae or Bartonellaquintana infection, primarily affecting immunocompromised individuals. The patient was treated successfully with oral doxycycline, resulting in the resolution of symptoms and lesions. BA is typically transmitted via cats and presents variably, including cutaneous angioproliferative lesions, hepatic or splenic involvement, and endocarditis. Diagnosis relies on histopathology with specialized staining and molecular testing, as culture and serologies are often insufficient. Treatment typically involves prolonged antibiotic therapy, emphasizing the importance of early recognition in immunosuppressed patients, including solid organ transplant recipients, to prevent complications.
Keywords: bacillary angiomatosis; angioproliferative lesions; Bartonella infection; immunocompromised patients; renal transplant recipients